2019
DOI: 10.3389/fnsys.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Coherence of Visual-Evoked Gamma Oscillations Is Disrupted by Propofol but Preserved Under Equipotent Doses of Isoflurane

Abstract: Previous research demonstrates that the underlying state of the brain influences how sensory stimuli are processed. Canonically, the state of the brain has been defined by quantifying the spectral characteristics of spontaneous fluctuations in local field potentials (LFP). Here, we utilized isoflurane and propofol anesthesia to parametrically alter the spectral state of the murine brain. With either drug, we produce slow wave activity, with low anesthetic doses, or burst suppression, with higher doses. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 79 publications
(102 reference statements)
0
13
0
4
Order By: Relevance
“…It is expected that brain activities are silenced and it becomes unresponsive to external stimuli during deep general anesthesia (Ries and Puil, 1993 ; Detsch et al, 1999 ). However, animal and human studies have demonstrated that brain still responds to somatosensory (Yli-Hankala et al, 1993 ), auditory (Land et al, 2012 ), and visual stimuli (Hartikainen et al, 1995 ; Hudetz and Imas, 2007 ; Aggarwal et al, 2019 ) under general anesthesia. The underlying mechanisms of anesthetic actions remain unknown, while it has been suggested that anesthetic-induced loss of consciousness and sleep have shared neural mechanisms (Franks and Zecharia, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that brain activities are silenced and it becomes unresponsive to external stimuli during deep general anesthesia (Ries and Puil, 1993 ; Detsch et al, 1999 ). However, animal and human studies have demonstrated that brain still responds to somatosensory (Yli-Hankala et al, 1993 ), auditory (Land et al, 2012 ), and visual stimuli (Hartikainen et al, 1995 ; Hudetz and Imas, 2007 ; Aggarwal et al, 2019 ) under general anesthesia. The underlying mechanisms of anesthetic actions remain unknown, while it has been suggested that anesthetic-induced loss of consciousness and sleep have shared neural mechanisms (Franks and Zecharia, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Se aplica la metodología de Bandt y Pompe con el propósito de evaluar la PDF para D = 3 y τ = 1. Los vectores (6,7,8), (7,8,13)…”
Section: Construcción Del Patrón Ordinal De Una Serie Temporalunclassified
“…Por lo tanto, mientras ambos anestésicos dejan a los sujetos inconscientes, la manera por los cual crean este estado puede surgir a través de diferentes mecanismos de red. Por ejemplo el efecto de las anestesias sobre las interneuronas podría ser muy diferente [7]. Utilizando las parametrizaciones de las señales usando las coordenadas θ podemos cuantificar la acción de ambas drogas, propofol e isoflurano, sobre la propagación de estas ondas evocadas visualmente.…”
Section: Discusión Y Conclusionesunclassified
See 2 more Smart Citations